Peran Sekolah Berbasis Pendidikan Karakter Terhadap Anak Yang Hyperaktif di RA Al-Hidayah - Elis Setiawati; Aang Andi Kuswandi; Evi Puspita Sari; Irmma Puspitasari Nurhadi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The purpose of this study was to determine the role of character education-based schools for hyperactive children at RA AL-HIDAYAH MARGACINTA, inhibiting factors for hyperactive children and supporting factors for the role of character education-based schools for hyperactive children at RA AL-HIDAYAH Margacinta. The method in this research is using the Field Research method where researchers go directly to the field. This type of research is qualitative with the case study Edu Happiness (Jurnal Ilmu Perkembangan Dini) Vol. 2 No. 1, Januari 2023 method. The location of this research was conducted at RA Al Hidayah, Margacinta Village, Cijulang District, Pangandaran Regency. road. When the teacher is talking, it often disturbs others, it is difficult to focus and sit still while eating or playing. The role of schools in handling hyperactive children is to take an approach that can also give specific assignments, give responsibility and direct productive activities. The inhibiting factors include the lack of strictness of the teacher, the professionalism of the teacher and the behavior of the children.